the Features of developing a strategy for the textile industry in the Republic of Uzbekistan: Features of developing a strategy for the textile industry in the Republic of Uzbekistan - Kadirkhodjaeva, Nilufar (Архив научных исследований, 2021)
Abstract: This article is the result of a dissertation research in the management and strategy development of the textile industry. This article deeply discusses the problems affecting the efficiency of the enterprise, in particular the factors affecting the implementation of the developed strategy. It should be noted that the external environment has a direct impact on the strategy of enterprises, but at the same time it is necessary to take into account the internal environment of the enterprise, which also has a certain influence on both the development of the strategy and its effective implementation. It is this article that is the result of a study of the effectiveness of the textile industry strategy in terms of both external and internal harvest.